Combined impact of silver nanoparticles and chlorine on the cell integrity and toxin release of Microcystis aeruginosa. (June 2021) - Singh, Abhishek; Hou, Wen-Che; Lin, Tsair-Fuh
Abstract: Silver nanoparticles (AgNPs) have shown to be toxic to freshwater cyanobacterial species, and sodium hypochlorite (NaOCl) is a common oxidant for the treatment of cyanobacterial cells. AgNPs have a high possibility of co-existing with the cyanobacterial cells in the aqueous environments leading to its exposure to NaOCl during water treatment; however, their combined effects on the cyanobacterial cells are largely undocumented. This work compares the individual and combined effect of AgNP and NaOCl on the integrity and toxin (microcystins) release of Microcystis aeruginosa at varying levels. The results show that the AgNP (0.2–0.6 mg/L) alone has negligible effects on the cell lysis, while NaOCl alone shows concentration-dependent (0.2 < 0.4 < 0.6 mg/L) rupturing of cells. In contrast, the AgNP + NaOCl (0.2–0.6 mg/L) samples show increasing loss in cell integrity at higher AgNP (0.4 and 0.6 mg/L) levels than the NaOCl only samples. NaOCl exposure results in increasing dissolution of AgNPs with time, releasing silver ions (Ag + ), affecting its size and morphology. The cell-associated total Ag declines over time with an increase in NaOCl levels, maybe due to increasing cell-lysis or NaOCl induced oxidative dissolution of AgNPs. The cell-associated total Ag and released Ag + possibly weaken the cellular membrane, thus assisting NaOCl in faster cell-lysis. The combined exposure of AgNP and NaOCl also results in a higher release of toxin from the cells. This work collectively reveals that the AgNPs combined with NaOCl can enhance the cell lysis and release of toxins. Graphical abstract: Image 1 Highlights: The combined effect of AgNPs and NaOCl on Microcystis aeruginosa is studied . Joint exposure of AgNPs and NaOCl enhances the cell-lysis. The enhanced cell rupture is AgNP concentration-dependent. The joint exposure could increase the release of intracellular microcystins.